Influence of ice templating on oxygen reduction catalytic activity of metal-free heteroatom-doped mesoporous carbon derived from polypyrrole for zinc-air batteries - Kurian, Maria; Ghosh, Meena; Vijayakumar, Vidyanand; Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Kurungot, Sreekumar (Energy Technology, 2022)
The development of highly active, cost-effective, and durable, noble metal-free oxygen reduction electrocatalysts is inevitable for the full-fledged implementation of fuel cells and zinc-air batteries. This work reports the synthesis of heteroatom (N, P, S)-doped metal-free mesoporous carbon-based electrocatalyst derived from polypyrrole by combining the ice templating, freeze-drying, and carbonization processes. The correlation between the structure and electrochemical activity of the polypyrrole-derived carbon-based electrocatalyst in the presence and absence of ice templating is investigated. The optimized electrocatalyst, aided by the ice-templating and freeze-drying step, shows an onset and half-wave potential (E-1/2) of 0.94 and 0.78 V vs reversible hydrogen electrode, respectively, in an alkaline electrolyte (0.1 m KOH). Later, the application of the optimized electrocatalyst is demonstrated in a primary zinc-air battery (ZAB) cell. The results prove that the ZAB device performance based on the homemade catalyst is on par with that of the state-of-the-art Pt/C cathode. The catalyst performance is correlated with the heteroatom doping and the enhanced porosity of the sample benefitted from ice templating. Ultimately, this work depicts a facile and rational synthesis of a truly metal-free electrocatalyst for the primary ZABs that can be a potential replacement for state-of-the-art systems.
Keywords: metal-free electrocatalysts; oxygen reduction reaction; zinc-air batteries

Binder-free and flexible VOPO4/CNT film as cathode for aqueous rechargeable Zn-metal battery - Dilwale, Swati; Babu, Athira; Puthiyaveetil, Priyanka Pandinhare; Kurian, Maria; Ghosh, Meena; Kurungot, Sreekumar (Advanced Sustainable Systems, 2023)
Aqueous rechargeable Zn-metal batteries (AZMBs) are promising energy storage aids due to their inherent safety, low cost, and competent performance, with prospects in stationary and portable applications. In this regard, one of the critical requirements is developing electrodes that can adapt to mechanical deformation without compromising the charge storage performance. The current work demonstrates the development of a binder-free and mechanically flexible composite cathode film (VP/fCNT-F, where `F' stands for the film) based on VOPO4 (VP) and functionalized carbon nanotubes (fCNTs). The VP/fCNT-F film processing involves simple vacuum filtration of the composite obtained from the in-situ reaction of the fCNTs and the VP precursor in an aqueous medium. The functionalization of carbon nanotube (CNT) is important for the homogenous dispersion of VP and fCNT. The VP/fCNT-F electrode is used as a monolithic electrode in AZMB cells in combination with both liquid and quasi-solid-state gel polymer electrolytes. Besides, the utility of the VP/fCNT-F electrode in a flexible battery configuration is also demonstrated. Interestingly, in both the coin-cell and flexible configurations, the VP/fCNT-F electrode delivers a comparable discharge capacity of 90 and 78 mAh g(-1), respectively (at 0.1 A g(-1)), validating the advantage of the binder-free VP/fCNT-F electrode for AZMBs.
Keywords: binder-free cathodes; flexible batteries; layered VOPO4; polymer gel electrolytes; self-standing flexible films

Donor-acceptor-based two-dimensional polymer as a supercapacitor electrode with long cycling stability - Bhagyasree, T. M.; Puthiyaveetil, Priyanka Pandinhare; Kumar, Viksit; Asokan, Kiran; Sreekumar, K.; Babu, Sukumaran Santhosh (New Journal of Chemistry, 2023)
The high demand for energy and energy-storage devices urged organic 2D polymers as a potential candidate in this area. One of the major attractions of 2D polymers in electrochemical applications is their long cycling stability due to their rigid and porous structure. Herein, we developed a 2D polymer comprised of donor-acceptor units exhibiting reasonably good performance as a supercapacitor. The 2D polymer displayed a maximum specific capacitance of 218 F g-1 at a current rate of 0.1 A g-1, a higher power density of 4648.35 W kg-1, and an energy density of 7.05 W h kg-1. In a cycling stability test, it demonstrated a capacitance retention of 70% over 10 000 continuous charge-discharge cycles at a current rate of 2.5 A g-1. Such long cycling stability was attributed to the donor-acceptor units and the crystalline nature of the polymer. The sensible selection of the building blocks of the 2D polymers is crucial for the performance and hence provides scope for improvement. An organic donor-acceptor-based 2D polymer, a promising candidate for energy storage devices, displays a specific capacitance of 218 F g-1, a power density of 4648.35 W kg-1, an energy density of 7.05 W h kg-1, and a capacitance retention of 70% over 10 000 cycles.

Cathode|electrolyte interface engineering by a hydrogel polymer electrolyte for a 3D porous high-voltage cathode material in a quasi-solid-state zinc metal battery by in situ polymerization - Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Dilwale, Swati; Kanheerampockil, Fayis; Kurungot, Sreekumar (SMALL, 2024)
This work highlights the development of a superior cathode|electrolyte interface for the quasi solid-state rechargeable zinc metal battery (QSS-RZMB) by a novel hydrogel polymer electrolyte using an ultraviolet (UV) light-assisted in situ polymerization strategy. By integrating the cathode with a thin layer of the hydrogel polymer electrolyte, this technique produces an integrated interface that ensures quick Zn2+ ion conduction. The coexistence of nanowires for direct electron routes and the enhanced electrolyte ion infiltration and diffusion by the 3D porous flower structure with a wide open surface of the Zn-MnO electrode complements the interface formation during the in situ polymerization process. The QSS-RZMB configured with an integrated cathode (i-Zn-MnO) and the hydrogel polymer electrolyte (PHPZ-30) as the separator yields a comparable specific energy density of 214.14 Wh kg(-1) with that of its liquid counterpart (240.38 Wh kg(-1), 0.5 M Zn(CF3SO3)(2) aqueous electrolyte). Other noteworthy features of the presented QSS-RZMB system include its superior cycle life of over 1000 charge-discharge cycles and 85% capacity retention with 99% coulombic efficiency at the current density of 1.0 A g(-1), compared to only 60% capacity retention over 500 charge-discharge cycles displayed by the liquid-state system under the same operating conditions.
Keywords: cathode-electrolyte interface tuning; dendrite inhibition; epitaxial zinc deposition; hydrogel polymer electrolyte; In situ polymerization; Quasi solidstate rechargeable zinc metal battery

High-voltage symmetric supercapacitor electrodes via in situ synthesized multiwalled carbon nanotube-doped perylenebisimide-based donor-acceptor conjugate polymer P(PDI2OD-T2) - Wavhal, Aryan Anurath; Dilwale, Swati; Puthiyaveetil, Priyanka Pandinhare; Kakde, Navnath R.; Prakash, Medha; Kurungot, Sreekumar; Asha, S. K. (Journal of Physical Chemistry C, 2024)
This study presents the design and synthesis of a donor-acceptor pi-conjugated polymer composite P(PDI2OD-T2)/MWCNT tailored for high-voltage symmetric supercapacitor applications. The synthesis of P(PDI2OD-T2)/MWCNT was expedited by adopting a novel in situ polymerization technique that modifies the traditional Stille polymerization process. Incorporating approximately 33% by weight of multiwalled carbon nanotubes (MWCNT) into the polymer matrix, referred to as P-2, significantly enhances its conductivity, surface area, and porosity. These improvements in the material properties contribute to the superior electrochemical performance of the composites by promoting efficient electrolyte ion transport across the electrode-electrolyte interfaces. The symmetric supercapacitor devices fabricated with P-2 electrodes employing both liquid organic (LE-P-2||P-2) and quasi-solid-state gel (QSS- P-2||P-2) electrolytes demonstrate capacitance values of 85.4 and 84.2 F g(-1), respectively, at a current density of 0.25 A g(-1), while operating at a high-voltage window of 3.1 V. Moreover, these devices exhibit robust cycling stability, maintaining approximately 70% of their initial capacitance over 45,000 cycles with a coulombic efficiency of 96%. The successful demonstration of a quasi-solid-state symmetric supercapacitor underscores the potential of flexible energy storage solutions, as evidenced by a PMMA LiClO4 gel electrolyte prototype. This flexible device not only maintains structural integrity but also achieves an impressive power density of 18,600 W kg(-1) and an energy density of 112.4 Wh kg(-1), indicating its practical viability for real-world applications.

Insights on prussian blue analogue cathode material engineered with polypyrrole surface protection layer for aqueous rechargeable zinc metal battery - Puthiyaveetil, Priyanka Pandinhare; Nair, Aathira; Dilwale, Swati; Kurian, Maria; Joshi, Kavita; Kurungot, Sreekumar (Small, 2024)
One of the key intricacies against using Prussian blue analogues (PBAs) in aqueous batteries is their gradual dissolution in aqueous electrolytes, resulting in inadequate cycling stability. Besides, the rate capability of PBAs is limited due to their poor electrical conductivity. To overcome these challenges, it is essential to tune the physical and chemical properties of PBAs at the nano regime without affecting the inherent charge storage properties, especially at high-voltage operating conditions. Through this work, a strategy is demonstrated to enhance the electrochemical performance of vanadium-based PBA (V-PBA) by surface engineering using a conducting polymer nano-skin (V-PBA/PPy) for aqueous zinc metal batteries. The polypyrrole (PPy) nano-skin over the V-PBA nanoparticles acts as an electron percolation path to ameliorate the poor electronic conductivity of the otherwise pristine V-PBA. Interestingly, the V-PBA with an optimized polypyrrole coating (V-PBA/PPy-2) exhibits an enhanced specific capacity (173 mAh g-1 at 0.10 A g-1) than the pristine V-PBA counterpart (80 mAh g-1) and 85% capacity retention up to 500 cycles. The DFT calculation confirms the synergistic interaction between PPy and V-PBA and the presence of PPy favors the adsorption of Zn.
Keywords: aqueous rechargeable zinc metal battery; DFT; polypyrrole coating; Prussian blue analogue; surface protection layer

Phytic acid customized hydrogel polymer electrolyte and prussian blue analogue cathode material for rechargeable zinc metal hydrogel batteries - Dilwale, Swati; Puthiyaveetil, Priyanka Pandinhare; Babu, Athira; Kurungot, Sreekumar (Small, 2024)
Zinc anode deterioration in aqueous electrolytes, and Zn dendrite growth is a major concern in the operation of aqueous rechargeable Zn metal batteries (AZMBs). To tackle this, the replacement of aqueous electrolytes with a zinc hydrogel polymer electrolyte (ZHPE) is presented in this study. This method involves structural modifications of the ZHPE by phytic acid through an ultraviolet (UV) light-induced photopolymerization process. The high membrane flexibility, high ionic conductivity (0.085 S cm-1), improved zinc corrosion overpotential, and enhanced electrochemical stability value of approximate to 2.3 V versus Zn|Zn2+ show the great potential of ZHPE as an ideal gel electrolyte for rechargeable zinc metal hydrogel batteries (ZMHBs). This is the first time that the dominating effect of chelation of phytic acid with M2+ center over H-bonding with water is described to tune the gel electrolyte properties for battery applications. The ZHPE shows ultra-high stability over 360 h with a capacity of 0.50 mAh cm-2 with dendrite-free plating/stripping in Zn||Zn symmetric cell. The fabrication of the ZMHB with a high-voltage zinc hexacyanoferrate (ZHF) cathode shows a high-average voltage of approximate to 1.6 V and a comparable capacity output of 63 mAh g-1 at 0.10 A g-1 of the current rate validating the potential application of ZHPE. A novel phytic acid (PA) modulated zinc hydrogel polymer electrolyte (ZHPE) as an efficient electrolyte and separator for rechargeable Zn-metal hydrogel batteries (ZMHB) is designed. The zincophilic, and hydrogen bonding characteristics of ZHPE help in regulating uniform dendrite-free Zn-deposition over the Zn anode surface. ZHPE in combination with the developed high-voltage zinc hexacyanoferrate (ZHF) cathode performs as an efficient ZMHB. image
Keywords: high voltage cathode; high-conducting gel polymer electrolyte; phytic acid; rechargeable Zn-metal hydrogel batteries; Zn hydrogel polymer electrolyte

Advances in polymer electrolyte design strategies for highly efficient supercapacitors and Zn-based batteries - Puthiyaveetil, Priyanka Pandinhare; Babu, Athira; Kurian, Maria; Kurungot, Sreekumar (Chemical Communications, 2025)
Electrolytes play a crucial role in the performance of electrochemical energy storage systems, such as batteries and supercapacitors. Their main function is to act as a medium for ion transport between the electrodes, which is essential for the charge and discharge processes. Beyond this, the electrochemical performance of the device is strongly affected by the various properties of the electrolytes such as their ionic conductivity, chemical, thermal and electrochemical stability, chemical compatibility, etc. The intrinsic limitations of the aqueous electrolytes such as their decomposition during high voltage operations has led to the development of better electrolytes for batteries and supercapacitors. These included non-aqueous electrolytes, inorganic solid-state electrolytes, and gel polymer electrolytes. This feature article reviews the various approaches to designing a highly efficient polymer electrolyte for the targeted application along with the suitable device fabrication strategy adopted in the current literature to achieve a balanced electrochemical performance compared with a liquid electrolyte-based device.

Anode|electrolyte|cathode interface engineering to develop a robust zinc metal hydrogel battery - Dilwale, Swati; Babu, Athira; Kanheerampockil, Fayis; Torris, Arun; Puthiyaveetil, Priyanka Pandinhare; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
The poor electrode-electrolyte interfaces in quasi-solid-state zinc metal batteries often hinder Zn2+ ion transport due to the poor compatibility of the gel electrolyte with the electrodes. This report proposes a dual-interface engineering strategy across the anode, cathode, and separator using a single hydrogel polymer electrolyte (HPE). The integration of vanadyl phosphate functionalized carbon nanotubes (VP/fCNT) into a commercial glass fiber (GF) separator, followed by a thin hydrogel coating and UV-light photopolymerization, resulted in a dual-interface engineered cathode-separator-electrolyte structure (VP/IC-EGF). To mitigate the dendritic growth, an artificial solid electrolyte interface was developed on Zn foil (AEI@Zn). The engineered GF (EGF) demonstrates a room-temperature conductivity of 6.5 mS cm-1 and a high electrochemical stability window of 2.4 V vs. Zn|Zn2+. The symmetric cell with AEI@Zn|EGF|AEI@Zn exhibits exceptional plating/stripping stability over 1400 h at a current density of 0.1 mA cm-2 and a capacity of 0.1 mAh cm-2. Moreover, the low-volume cell (AEI@Zn & Vert;VP/IC-EGF), featuring the dual-interface-engineered cathode-separator-electrolyte, demonstrates outstanding cycling stability with over 3000 charge-discharge cycles at a current rate of 1.0 A g-1, retaining 98-99% of its initial capacity and showing high coulombic efficiency. These findings underscore the significant impact of interface engineering on enhancing the performance of ZMBs.

Insights into the structure and electrochemical properties of Ti3C2T x MXene from solid-state NMR - Balasubramanian, Rajalakshmi; Puthiyaveetil, Priyanka Pandinhare; Kurungot, Sreekumar; Ajithkumar, T. G. (Journal of Physical Chemistry C, 2026)
Ever since their discovery in 2011, MXenes have gained popularity in energy storage devices. Their far-reaching properties arise mainly due to surface terminations and interlayer species like hydrated cations and water. The nature of these species remains a subject of study due to the complex surface functionalization during synthesis. X-ray diffraction studies have shown that certain intercalants such as hydrated cations increase the interlayer spacing leading to enhanced electrochemical performance. However, the structural and chemical modification of these intercalants during the charge-discharge cycles of asymmetric supercapacitors are yet to be investigated. Analysis of the complex chemistry of Ti3C2Tx requires a specialized tool that can provide insights into its nuanced structural changes and link them to its behavior. In this study, we demonstrate the versatility of solid-state NMR (SSNMR), for the characterization of surface terminations and intercalants in the Ti3C2Tx MXene prepared using sodium salts, and correlate its structure to its performance by ex situ SSNMR analysis. Our experiments demonstrate the progressive oxidation of surface Ti-OH and also the significance of the intercalated hydrated cation shells during electrochemical cycling. In addition to this, we have also employed Na-23 MAS SSNMR to demonstrate the conversion of sodium hexahydrate to sodium peroxides after 10 charge-discharge cycles.

Self-healing hydrogel electrolyte enabled by dynamic polar covalent and noncovalent interactions for high-performance rechargeable zinc-metal batteries: a leap toward sustainable energy storage - Puthiyaveetil, Priyanka Pandinhare; Kurian, Rachna Maria; Samudre, Nikhil S.; Balasubramanian, Rajalakshmi; Torris, Arun; Pockil, Fayis Kanheeram; Bhat, Suresh; Ajithkumar, T. G.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Advanced Energy Materials, 2026)
Hydrogel polymer electrolytes with superior multifunctional properties are promising alternatives to aqueous electrolytes for resolving interfacial issues in rechargeable zinc-metal batteries. In this study, an intrinsic self-healing hydrogel polymer electrolyte (PHBC-4) is synthesized, engineered through an integrated approach involving the polar covalent (B & horbar;O bond), hydrogen-bond (polyvinyl alcohol-hydroxypropyl methylcellulose interface), and coordination-type (Zn & horbar;O) interactions to enable self-healing functionality. The PHBC-4 has demonstrated high ionic conductivity (4.6 x 10-2 S cm-1), good oxidative stability (2.3 V vs Zn|Zn2+), a high cation transference number (0.89), superior tensile strength (0.32 MPa), and an impressive healing efficiency of 93% achieved just within 5 min, confirming its robust self-healing capability. In Zn||Zn symmetric cells, it effectively suppresses dendrite growth, ensuring stable cycling for over 1032 h with an areal capacity of 1.0 mAh cm-2 at a current density of 1.0 mA cm-2. When paired with a Zn-doped MnO cathode in the rechargeable homemade pouch cell, the system delivers a high specific capacity of 160 mAh g-1 at 0.10 A g-1 and cycling stability up to 493 charge-discharge cycles at 2.0 A g-1. The self-healing ability of PHBC-4 HGPE is confirmed in a homemade pouch cell via OCV and charge-discharge tests, demonstrating stable performance. The DFT studies confirm molecular-level interactions within the hydrogel heterostructure.
Keywords: dendrite inhibition; flexible rechargeable zinc metal battery; high cation transference number; self-healing hydrogel polymer electrolyte